Generasi Perintis dan Penerus Studi Teori Kepartaian - Fadilah, Sariul; Satryo Pringgo Sejati (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Political parties are an important measure and condition for whether a country can be called a democracy or not. In other words, political parties in modern political life have become a very clear measure to see the level of democracy in a country. Political parties have become the most important representation of society's political power (political infrastructure) in modern political life for all countries that call themselves democracy country. The data collected from research sources is used as analytical data and to analyze the issues discussed, namely about the pioneering and succeeding generations which are based on a party theory. The development of the study of party theory has been tried to be traced from the pioneering generation that emerged at the beginning of the 20th century to its development until the 1990s. The explanation that the author has put forward in the discussion of this article is realized to be more focused on the development of the study of political parties that occurred in the Western world. The theories developed to date regarding political parties are still dominated by theories originating from the United States and parts of Europe. This condition raises concerns because theories originating from the west are not fully appropriate to the conditions of countries outside the United States and Europe.